Pendidikan Islam Dan Perkembangan Teknologi Informasi - matroni, matroni; Junaidi, Shidqi (Tasamuh: Jurnal Studi Islam, 2023)
In this research, we will focus on Islamic Education and the Development of Information Technology. This research is field research (Field research) in qualitative and library form by collecting data, as well as examining references related to the subject being studied, including papers, books, newspapers, journals. This type of research is qualitative research with a focus on library studies with examine the use of information technology to improve the quality of Islamic education in madrasas through the study of Koranic texts. or hadith, books, articles and manuscripts in the discussion description